PLANTS AND ANIMALS USED TO COMBAT THE COVID-19 PANDEMIC IN TWO INDIGENOUS TICUNA COMMUNITY IN THE DEPARTMENT OF LORETO, PERU. - MARTÍN BRAÑAS, Manuel (2022)
COVID-19 hit the Amazonian indigenous communities of Peru for two consecutive years, forcing them to recover traditional knowledge, practices and strategies to combat it. We present the plant and animal species used by two Ticuna communities in the Peruvian Amazon during the COVID-19 pandemic, describing the preparation and administration of the preparations. The information was obtained from semi-structured interviews with men and women from the communities during the first two waves of the pandemic, from May 2020 to June 2021. The interviews were face-to-face, in the field work carried out in the communities, and virtual, using the telephone and messaging applications available in the communities or in the nearby major population centers. During the field work in Nueva Galilea, visits were made to the collection points of the plant species. Fourteen plant species and three animal species used in the pandemic were identified. The most used parts of the plant species, in order of importance, were the leaves, roots, bulbs and fruits, making preparations in the form of infusions, fresh, in baths and in steam inhalations. It is evident how traditional knowledge in the use of plants and animals that heal, in an integrated manner with the appropriation of external knowledge, is still valid in the Ticuna communities. Knowledge about the healing properties of fourteen plant species and three identified animal species has made it possible to combat the symptoms of a very aggressive disease.